Two Cases of Q-Fever in Hairy Cell Leukemia - Emanuele Ammatuna; Emilio Iannitto; Lidwine W. Tick; Nicolaas L. A. Arents; Philip H. Kuijper; Marten R. Nijziel (Case Reports in Hematology)
Hairy cell leukemia (HCL) is a rare B-cell lymphoproliferative disorder accounting for about 2% of all leukemias. The clinical course is indolent, however HCL patients are particularly susceptible to infections. Here we report two cases of Q-fever as first manifestation of disease in two patients affected by HCL. Both patients described in this report showed an unusually sluggish clinical response to the antibiotic treatment with ciprofloxacin probably because of the marked immunodeficiency. However, treatment of HCL with cladribine administered soon after the resolution of QF pneumonitis was uneventful and led to a complete remission in both cases. Most probably the association of Coxiella burnetii (CB) infection and HCL that we observed in two patients is due to chance. However, a hairy cell resembling transformation of freshly isolated human peripheral blood lymphocytes upon CB has been showed. We think that the possibility of CB infection in febrile HCL patient should be always taken in mind, especially in endemic areas. In addition the potential for such infections to become chronic in HCL patients should not be overlooked and the reporting of further cases should be encouraged.